Pengaruh Penempatan Dan Kompetensi Sumber Daya Manusia Terhadap Kinerja Pegawai Pada Kantor Pengadilan Negeri Sorong - Ohorella, Dahlia; Pattiasina, Claudio; Kokmala, Martina (Jurnal Ilmiah Ilmu Manajemen, 2023)
The purpose of this study is to determine the effect of placement and competence of human resources in the Sorong district court office. This study used quantitative methods with data collection techniques used, namely distributing questionnaires to consumers as many as 40 people. The results of this study were collected through questionnaires that were processed and analyzed using Multiple Regression. Then conducting data quality tests used are validity tests, reliability tests, classical assumption tests, normality tests, heterokedasticity tests, multiple linear regression analysis, t tests, F tests and determination coefficient analysis. Tools used Microsoft Excel and SPSS Software. The results showed that placement and competence had a significant effect on employee performance.